Fundamentalna grupa in koH-prostori - Franc, Aleksandra (Obzornik za matematiko in fiziko, 2009)
After a quick revision of necessary algebraic definitions we explain the concept of the fundamental group in some detail. In the main section we define coH-spaces and prove that the fundamental group of a coH-space is free. Finally, we present some recent results concerning the fundamental groups of manifolds.
Keywords: algebraična topologija; fundamentalne grupe; matematika